2020
DOI: 10.14295/bds.2020.v23i2.2255
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular disorders: Guidelines and Self-Care for Patients During COVID-19 Pandemic

Abstract: Background: Temporomandibular disorder (TMD) belongs to a heterogeneous group of musculoskeletal and neuromuscular conditions involving the temporomandibular joint complex, musculature and adjacent components. These conditions can generate signs and symptoms and be influenced by an altered biopsychosocial condition. Objective: This study aims to seek information to assist the patient in the presence of TMD signs and symptoms and Orofacial Pain, associated with the period of social isolation during the COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 27 publications
0
14
0
2
Order By: Relevance
“…In this scenario, dentists must use individualized strategies, while considering the multifactorial etiology. They should adapt to individual circumstances and utilize various treatment methods, including sleep hygiene management, physical exercise, self-massage, and "teledentistry" (Oliveira et al, 2020). Therefore, it is suggested that university students of dental school, given their vulnerability to such dysfunctions, be included in the planning of approaches for the prevention of onset and worsening of TMD.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, dentists must use individualized strategies, while considering the multifactorial etiology. They should adapt to individual circumstances and utilize various treatment methods, including sleep hygiene management, physical exercise, self-massage, and "teledentistry" (Oliveira et al, 2020). Therefore, it is suggested that university students of dental school, given their vulnerability to such dysfunctions, be included in the planning of approaches for the prevention of onset and worsening of TMD.…”
Section: Discussionmentioning
confidence: 99%
“…Psychosocial factors such as anxiety and stress are recognized to be associated mainly with the awake form of bruxism [25], which is characterized by the parafunctional activity of clenching the teeth while the patient are awake and without necessarily being conscious of performing it [26,27]. Patients diagnosed with elevated stress levels are up to 6 times more likely to develop this condition [19,28]. Recently some authors suggested that muscle contraction in awake bruxism may be part of the body's defense behavior mechanism associated with anxiety and stress, increasing significantly in this period of the pandemic [28].…”
Section: Parafuncional Habitsmentioning
confidence: 99%
“…Patients diagnosed with elevated stress levels are up to 6 times more likely to develop this condition [19,28]. Recently some authors suggested that muscle contraction in awake bruxism may be part of the body's defense behavior mechanism associated with anxiety and stress, increasing significantly in this period of the pandemic [28]. Obstructive sleep apnea and hypopnea syndrome (OSAS) is one of the recognized risk factors for protective sleep bruxism.…”
Section: Parafuncional Habitsmentioning
confidence: 99%
“…Recentemente jornais e mídias sociais noticiaram o aumento de fraturas dentais associado a maior apertamento durante a quarentena (S. S. I. de Oliveira et al, 2020). Ainda, portadores de bruxismo, seja ele em vigília ou noturno (durante o sono) apresentam sintomas que interferem no seu bem estar, como dores na face, alterações na qualidade do sono, e maior chance de ocorrência de hipersensibilidade dentária (HD).…”
Section: Aspectos Sociais E Comportamentaisqual a Relevância?unclassified